2011
DOI: 10.1007/s10549-011-1631-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations among baseline variables, treatment-related factors and health-related quality of life 2 years after breast cancer surgery

Abstract: Provision of social support and rehabilitation for patients with physical, mental and functional problems after cancer treatment is important for long-term health-related quality of life (HRQOL). Effective use of human and financial healthcare resources requires identification of patients requiring rehabilitation. The objectives of the current study were to clarify the patterns of physical and psychosocial recovery over time, to evaluate the associations among baseline variables, treatment-related factors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 50 publications
7
74
0
9
Order By: Relevance
“…Previous studies also reported the same finding (17,19,21). Family members, particularly spouses, can provide ill people with the necessary social support for coping with their illnesses.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies also reported the same finding (17,19,21). Family members, particularly spouses, can provide ill people with the necessary social support for coping with their illnesses.…”
Section: Discussionsupporting
confidence: 68%
“…We asked the participants to respond to the Functional Assessment of Cancer Therapy-breast (FACT-B) [20,21] and -taxane (FACT-T) subscale [13,22] questionnaires at baseline, on day 1 of cycles 3, 5 and 7, and 7 and 12 months after enrollment. QOL was assessed either at the 7-month time point or 1–2 months after completion of the protocol-specified 8th cycle of treatment to collect data when the patients had somewhat recovered from the invasive treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were asked to voluntarily and anonymously participate and give informed consent by completing and returning the questionnaire. In order to collect baseline variables, questions were formulated based on personal and medical factors which may influence a patient's psychological outcome (15). Only the medical researcher knew which study number belonged to which patient.…”
Section: Data Collectionmentioning
confidence: 99%